1999
DOI: 10.1111/j.1574-695x.1999.tb01330.x
|View full text |Cite
|
Sign up to set email alerts
|

Sudden infant death syndrome, virus infections and cytokines

Abstract: Many epidemiological risk factors identified for sudden infant death syndrome (SIDS) suggest a viral aetiology, e.g. exposure to cigarette smoke and winter peak, mild respiratory symptoms. Virus infections and bacterial toxins induce cytokine activity and it has been suggested that uncontrolled inflammatory mediators could be involved in some cases of SIDS. The aim of this review was to assess the evidence for virus infection in SIDS and to examine those findings in relation to individual variations in cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 130 publications
2
25
0
Order By: Relevance
“…In Australia, common fetal pathogens include CMV, HSV, rubella virus, T. gondii and VZV (1,9,10,28,40). To our knowledge, there is no universal screening for any of these infections, and diagnosis is often difficult, particularly as detailed viral testing in this country is rarely performed in intrauterine deaths (40), in neonates and even in postnatal death from sudden infant death syndrome (23,41).…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, common fetal pathogens include CMV, HSV, rubella virus, T. gondii and VZV (1,9,10,28,40). To our knowledge, there is no universal screening for any of these infections, and diagnosis is often difficult, particularly as detailed viral testing in this country is rarely performed in intrauterine deaths (40), in neonates and even in postnatal death from sudden infant death syndrome (23,41).…”
Section: Discussionmentioning
confidence: 99%
“…Episodes of marked hypoxaemia often occur during respiratory infection and this combination of stressors poses an appreciable risk to the newborn [9] . The major finding of the study was that LPS combined with hypoxia treatment had a greater effect on brain allopregnanolone concentrations in the majority of brain regions examined, than did either of the treatments alone.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that hypoxia alters arousal, particularly during the newborn period when hypoxic events due to respiratory and cardiovascular instability is relatively common [9] . We have recently reported that episodes of asphyxia during fetal life markedly increase allopregnanolone concentrations in the developing brain [15] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 In the ensuing years, all SIDS hypotheses essentially invoked defective respiratory or autonomic mechanisms. 27,30,[51][52][53][54][55][56][57][58] The roles of respiratory and autonomic pathways in SIDS are not mutually exclusive, given that infants who subsequently died of SIDS have frequently been found to have subclinical deficits in both respiratory and autonomic function. [59][60][61] Ultimately, SIDS appears to involve failed defense mechanisms, with sleep in some important way unmasking the underlying vulnerability.…”
Section: Putative Terminal Pathways For Sidsmentioning
confidence: 99%